2019
DOI: 10.1093/aobpla/plz022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on young plants of Virola surinamensis

Abstract: Identification of native Amazonian tree species with potential for phytoextraction and tolerance to cadmium (Cd) can be used to direct studies and phytoremediation programs for preservation of natural areas and restoration of environments contaminated by heavy metals. The study evaluated the physiological responses and the phytoextraction and tolerance capacity of young plants of Virola surinamensis to Cd. We founded that Virola surinamensis showed medium and high tolerance to Cd and low efficacy in Cd phytoex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…An excluder transforms the metals and metalloids into a less toxic mobile form without extracting them from the soil and accumulates these compounds in roots by absorption or precipitation within the rhizosphere [ 84 ]. Recently, promising results of Virola surinamensis for Cd phytostabilization have been documented [ 85 ]. Likewise, Miscanthus x giganteus [ 86 ], and oats and white mustard [ 87 ] also have phytostabilization potential for Cd.…”
Section: Phytoremediation Processes and Their Salient Featuresmentioning
confidence: 99%
“…An excluder transforms the metals and metalloids into a less toxic mobile form without extracting them from the soil and accumulates these compounds in roots by absorption or precipitation within the rhizosphere [ 84 ]. Recently, promising results of Virola surinamensis for Cd phytostabilization have been documented [ 85 ]. Likewise, Miscanthus x giganteus [ 86 ], and oats and white mustard [ 87 ] also have phytostabilization potential for Cd.…”
Section: Phytoremediation Processes and Their Salient Featuresmentioning
confidence: 99%
“…In addition, the sugar transported to the roots because of starch degradation would be an essential energy substrate for the resumption of respiration, conferring a mechanism of tolerance of the plant against the phytotoxic effect of Cd (Rahoui et al 2015). Studies conducted by Andrade Júnior et al (2019) indicated that V. surinamensis presented medium and high tolerance to Cd. Similar results in the reducing sugar concentration have been found in other species (Shah et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that higher plants are more sensitive to Cd stress (Xie et al 2014). However, study conducted by Andrade Júnior et al (2019) demonstrated medium and high tolerance of Virola surinamensis to Cd. Variations in Cd tolerance in plants may be associated with changes in nitrogen and or carbon metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations